Influence of short distance transportation on tracheal bacterial content and lower airway cytology in horses. (August 2016) - Allano, Marion; Labrecque, Olivia; Rodriguez Batista, Edisleidy; Beauchamp, Guy; Bédard, Christian; Lavoie, Jean-Pierre; Leclere, Mathilde
Highlights: In a prospective study, healthy horses were transported for 2.5 h, with or without hay. Transportation had no effect on tracheal cytology and bacterial count. Bronchoalveolar lavage neutrophilia was observed after transportation without hay. Delaying sampling for cytology after transportation should be considered. Abstract: The aim of this study was to determine the effects of short distance transportation on airway mucus, cytology and bacterial culture to identify potential biases in the diagnosis of airway diseases in referral centres. Eight healthy adult horses were studied using a prospective cross-over design. Mucus scores, tracheal wash (cytology, bacterial culture) and bronchoalveolar lavage fluid (BALF; cytology) were obtained while stabled and following 2.5 h transportation (with and without hay). Neutrophil counts, percentages and BALF neutrophilia frequency increased following transport without hay ( P  <   0.05). No effect was observed on tracheal cytology and bacterial count ( P  > 0.05). BALF neutrophilia could develop solely as a result of transportation or due to interactions between repeated transports, ambient temperature, head position or other environmental factors.